The Increase in The Results of The Study and The Activity of Learners Through The Method of Discovery Learning in Mathematics - Miza Emylina (International Journal of Educational Dynamics, 2019)
Abstract The background study of mathematics in the sixth grade at SDN 10 Nan Balimo districk of Tanjung Harapan Solok city,where teachers mostly use the lecture method and learning tasks.During these learning out comes visible only from the ability of learnes to memorizefacts. Although many students are able to present a good level of memorization of the material it receives,but in reality they often do not understand in depth the substance of the material.Therefore conducted research in the form of precycle,cycle I and cycle II.There are four important satges in this action research,that is : (1) Design, (2) implementation, (3) observation, (4) reflection, Arikunto,dkk ( 2006 : 20 )at SDN 10 Nan Balimo,changes in learning shown by mastering by learnes. Effective learning activities cannot appear by itself but the teacher should be able to create learning that enables learnes archieve the goals that have been set optimally,improvement of learning out comes of student and interest of learnes to be able to understand learning materials using a makeshift media and methods that are less precise at first was somewhat less but after improvements both in terms of teaching methode and used the students interest and understanding of the learning material has begin to rise, and with the use of mathematical methods of discovery learning outcomes of students at SDN 10 Nan Balimo already increased due to the discovery method required students to find themselves in everyday life. Keywords : learning outcome,methods of Discovery,learning of mathematics